Reading the Old Textile Factory Complex of Antalya in Terms of Urban Memory and Current Spatial Experience - Kavas, Kemal Reha (ICONARCH International Congress of Architecture and Planning, 2017)
Antalya, which is situated in the Mediterranean region of Turkey, has become an internationally recognized center of tourism since the 1980s. In Antalya, which is associated mainly with the sectors of tourism and agriculture today, there has been public investments in industry between the 1960s and 1980s. The textile factory, which has given its name to the “Dokuma” (weaving) district where it was established, is a representative of this period’s industrial heritage in urban space. The factory, which was active between the early 1960s and 2000s, consists of a large complex of buildings with divergent functions and this complex is an important element influencing the urban scale. During its almost 40 years of performance, it established a continuous institutional culture. The factory became an active cultural agent shaping urban space because it has become the initiator of a large urban district which did not exist before. The deep imprints of the factory in the urban memory can still be felt. After a controversial process, in 2015 preservation and re-functioning was considered officially. In consequence, the green areas were opened to public use for recreational purposes. The re-functioning of the buildings is a continuing process which has not been implemented yet. Therefore regarding the old factory complex, current spatial experience of the citizens is a matter of discussion and this experience is underlined principally by recreational function. This study reveals the relation between urban memory and current spatial experience in the specific context of the factory and proposes solutions for possible discrepancies.